Regional Household and Poverty Effects of Russia's Accession to the World Trade Organization - Rutherford, Thomas; Tarr, David (World Bank, Washington, DC, 2012)
This paper develops a seven-region comparative static computable general equilibrium model of Russia to assess the impact of accession to the World Trade Organization on these seven regions (the federal okrugs) of Russia. In order to assess poverty and distributional impacts, the model includes ten households in each of the seven federal okrugs, where household data are taken from the Household Budget Survey of Rosstat. The model allows for foreign direct investment in business services and endogenous productivity effects from additional varieties of business services and goods, which the analysis shows are crucial to the results. National welfare gains are about 4.5 percent of gross domestic product in the model, but in a constant returns to scale model they are only 0.1 percent. All deciles of the population in all seven federal okrugs can be expected to significantly gain from Russian World Trade Organization accession, but due to the capacity of their regions to attract foreign direct investment, households in the Northwest region gain the most, followed by households in the Far East and Volga regions. Households in Siberia and the Urals gain the least. Distribution impacts within regions are rather flat for the first nine deciles; but the richest decile of the population in the three regions that attract a lot of foreign investment gains significantly more than the other nine representative households in those regions.